Prognostic Value of the Tricuspid Regurgitation Impact on Outcomes (TRIO) Score in Patients Undergoing Transcatheter Aortic Valve Implantation - Jizhong Wang; Yuanwei Chen; Xuxing Zhang; Songyuan Luo; Jie Li; Fang Pei; Jianfang Luo (Reviews in Cardiovascular Medicine)
Background: Prognosis assessments for transcatheter aortic valve implantation (TAVI) patients remain challenging, particularly as the indications for TAVI expand to lower-risk patients. This study assessed the prognostic value of the tricuspid regurgitation impact on outcomes (TRIO) score in patients after TAVI. Methods: This single-center study included 530 consecutive patients who underwent TAVI. Patients with a TRIO score >4 were compared to those with a score ≤4. The primary outcome was all-cause mortality, while secondary outcomes included complications defined by the Valve Academic Research Consortium 2 (VARC-2) criteria and major adverse cardiovascular events (MACEs), including mortality, stroke, and heart failure rehospitalization. Results: Over a mean follow-up period of 22 months, patients with a TRIO score >4 had significantly higher rates of mortality (11.5% vs. 3.1%, p < 0.001) and MACEs (14.9% vs. 3.6%, p < 0.001). Multivariable Cox regression analysis identified a TRIO score >4 as an independent risk factor for all-cause mortality (hazard ratio (HR): 2.41, 95% confidence interval (CI): 1.08–5.37, p = 0.032) and MACEs (HR: 2.78, 95% CI: 1.34–5.75, p = 0.006). Patients with a higher TRIO score also had significantly higher rates of stroke (3.1% vs. 0.5%, p = 0.028), acute kidney injury (10.1% vs. 4.3%, p = 0.011), and MACEs (14.9% vs. 3.6%, p < 0.001) within 30 days after TAVI. Conclusions: The TRIO score was associated with all-cause mortality and MACEs in patients after a TAVI. The TRIO score could serve as a convenient tool for risk stratification in clinical practice, aiding in identifying high-risk patients.